Device impact of photon recycling and luminescent coupling on InGaP/Si tandems - Ren, Zekun; Mailoa, Jonathan P.; Liu, Zhe; Liu, Haohui; Sofia, Sarah E.; Sahraei, Nasim; Siah, Sin Cheng; Lin, Fen; Buonassisi, Tonio; Peters, Ian Marius (2015 IEEE 42nd Photovoltaic Specialist Conference, PVSC 2015, 2015)
We numerically evaluate the device impact of photon re-absorption on InGaP/Si tandem solar cells using a coupled optical-electronic device model. The presented simulation results provide guidelines for designing high performance InGaP/Si tandem device. We find that including the effects of photon recycling (PR) and luminescent coupling (LC) results in a 12.5% increase in optimum top-cell thickness for a two-terminal configuration. Furthermore, PR and LC affect the sensitivity of the tandem's conversion efficiency to various device parameters. As the InGaP bulk lifetime increases, there is an absolute efficiency increase of up to 0.7% for the two-terminal as well as the four-terminal configuration. Considering PR and LC furthermore reduces the power generation sensitivity to shunting in the two-terminal configuration. For the four-terminal configuration, photon re-absorption has a less significant impact.
CRIS-Team Scopus Importer:2023-03-07
Keywords: III-V solar cell; Luminescent coupling (LC); photon recycling (PR); Si solar cell